2021
DOI: 10.21203/rs.3.rs-144450/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the Long non-coding RNA ZFAS1 attenuates pathogenic ferroptosis by sponging miR-150-5p to activate CCND2 against diabetic cardiomyopathy

Abstract: Background Diabetic cardiomyopathy (DCM) needs to be responsible for the increasing morbidity and mortality in diabetic patients with heart failure. Unfortunately, the pathogenesis of DCM has yet to be elaborate. Here we investigate the important role of lncRNA-ZFAS1 in the pathological process of DCM associated with ferroptosis. Methods Microarray data analysis of DCM in the patients or mice model from GEO was presented that ZFAS1 was significantly upregulated, miR-150-5p and CCND2 were significantly downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Ni et al found that lncRNA-ZFAS1 as a ceRNA sponge miR-150-5p can regulate CCND2, thereby promoting ferroptosis in diabetic cardiomyopathy (DCM). Inhibiting lncRNA-ZFAS1 leads to decreased collagen deposition, decreased cardiomyocyte apoptosis and ferroptosis, and the progress of DCM weakened [ 76 ]. DOX promotes the activity of lncRNA KCNQ1OT1 by upregulating the expression of METL14, thereby inhibiting the activity of miR-7-5p, increasing the level of transferrin receptor, promoting iron absorption and the production of lipid reactive oxygen species, and inducing cardiomyocyte ferroptosis [ 77 ].…”
Section: Regulation Of Noncoding Rna On Ferroptosis In Cvdmentioning
confidence: 99%
“…Ni et al found that lncRNA-ZFAS1 as a ceRNA sponge miR-150-5p can regulate CCND2, thereby promoting ferroptosis in diabetic cardiomyopathy (DCM). Inhibiting lncRNA-ZFAS1 leads to decreased collagen deposition, decreased cardiomyocyte apoptosis and ferroptosis, and the progress of DCM weakened [ 76 ]. DOX promotes the activity of lncRNA KCNQ1OT1 by upregulating the expression of METL14, thereby inhibiting the activity of miR-7-5p, increasing the level of transferrin receptor, promoting iron absorption and the production of lipid reactive oxygen species, and inducing cardiomyocyte ferroptosis [ 77 ].…”
Section: Regulation Of Noncoding Rna On Ferroptosis In Cvdmentioning
confidence: 99%